Aluminum ion battery negative electrode and aluminum ion battery
By setting silicone rubber and its derivative coating on the negative electrode substrate of the aluminum ion battery, the exchange current density is regulated, and the problems of uneven deposition and short circuit of aluminum metal in aluminum ion battery are solved, and the cycle life and Coulomb efficiency are improved.
Patent Information
- Application Number
- CN202411642525.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
When charging, aluminum ion batteries cause uneven deposition of aluminum metal due to uneven current density on the electrode surface, resulting in large particles of aluminum and aluminum dendrites, which easily pierce the diaphragm and cause short circuits, reducing cycle life and Coulomb efficiency.
Silicone rubber and its derivative coating are provided on the negative electrode substrate of the aluminum ion battery, and the coating thickness is controlled within the range of 0.1 μm to 20 μm, the exchange current density on the surface of the negative electrode is regulated, and the deposition of large-particle aluminum and the formation of aluminum dendrites are reduced.
Through uniform aluminum metal deposition, short circuit phenomenon is reduced, and the cycle life and Coulomb efficiency of aluminum ion batteries are improved.
Smart Images

Figure CN119480898A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum ion batteries, and in particular to aluminum ion batteries and aluminum ion batteries. Background Art
[0002] In recent years, with the rapid development of social economy, the demand for green energy development has become increasingly high, and promoting energy transformation and developing renewable energy has become a global consensus. Energy storage technology, as the key to achieving large-scale application of clean energy, has attracted widespread attention. Among many energy storage technologies, lithium-ion batteries have been widely used in mobile devices, electric vehicles, and renewable energy fields due to their advantages such as high energy density, long cycle life, low self-discharge rate, no memory effect, and environmental friendliness. However, lithium-ion batteries still have problems such as high cost, limited lithium resources, and decreased safety performance in high temperature environments, which limit their application prospects in large-scale energy storage systems.
[0003] Aluminum is the most abundant metal element in the earth's crust. Compared with lithium, its resources are more extensive and cheaper. Compared with lithium-ion batteries, aluminum-ion batteries have lower costs and higher safety performance, and the theoretical volume capacity and mass capacity of aluminum metal are as high as 8048mAh·cm -3 and 2981mAh·g -1 Therefore, aluminum-ion batteries have broad application prospects in the next generation of large-scale energy storage systems.
[0004] In aluminum-ion batteries, the negative electrode of the aluminum-ion battery undergoes an electrochemical deposition reaction during charging. During the deposition process, the uneven current density on the electrode surface will cause uneven deposition of aluminum metal on the negative electrode surface, and large particles of aluminum and aluminum dendrites will easily form on the electrode surface. These large particles of aluminum and aluminum dendrites can easily pierce the diaphragm, causing the battery to short-circuit, leading to a decrease in battery cycle life and coulombic efficiency. Summary of the invention
[0005] The present application provides an aluminum ion battery negative electrode and an aluminum ion battery. The aluminum ion battery negative electrode of the present application includes a negative electrode substrate and a silicone rubber and its derivative coating located on the surface of the negative electrode substrate. During the electrochemical deposition reaction of the aluminum ion battery, the silicone rubber and its derivative coating can improve the deposition uniformity of aluminum metal on the surface of the aluminum ion battery negative electrode; at the same time, by controlling the thickness of the coating, the exchange current density on the surface of the aluminum ion battery negative electrode can be regulated, and the deposition of large aluminum particles and the generation of aluminum dendrites on the surface of the aluminum ion battery negative electrode can be reduced, thereby reducing the occurrence of short circuit phenomenon in the aluminum ion battery and improving the cycle life and coulomb efficiency of the aluminum ion battery.
[0006] In a first aspect, an embodiment of the present application provides an aluminum ion battery negative electrode, which includes a negative electrode substrate and a coating located on the surface of the negative electrode substrate, wherein the coating includes silicone rubber and its derivatives, and the thickness of the coating is 0.1 μm to 20 μm.
[0007] In some embodiments, the silicone rubber and its derivatives include at least one of polydimethylsiloxane, methylvinyl silicone rubber, phenyl silicone rubber, fluorosilicone rubber and nitrile silicone rubber.
[0008] In some embodiments, the coating has a thickness of 0.2 μm to 2 μm.
[0009] In some embodiments, the negative electrode substrate includes at least one of aluminum foil, copper foil, stainless steel foil, titanium foil, nickel foil, molybdenum foil, nickel foam, copper foam, and aluminum foam.
[0010] In a second aspect, an embodiment of the present application provides an aluminum ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode is the negative electrode of the aluminum ion battery described in the first aspect.
[0011] In some embodiments, the electrolyte includes an ionic liquid electrolyte and / or a deep eutectic solvent.
[0012] In some embodiments, the ionic liquid electrolyte includes aluminum chloride and imidazolium salt system.
[0013] In some embodiments, the deep eutectic solvent includes at least one of aluminum chloride and caprolactam, aluminum chloride and urea, aluminum chloride and N-alkylurea, aluminum chloride and acetamide, aluminum chloride and triethylamine, aluminum chloride and pyridine, aluminum chloride and pyridine chloride, aluminum chloride and alkylamine hydrochloric acid, aluminum chloride and acrylamide, and aluminum chloride and thiourea.
[0014] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:
[0015] The aluminum ion battery negative electrode provided by the present application includes a negative electrode substrate and a silicone rubber and its derivative coating arranged on the negative electrode substrate. During the electrochemical deposition reaction of the aluminum ion battery negative electrode, the Si-O bonds in the silicone rubber and its derivative coating are partially destroyed in the electrolyte to form Al-O bonds, thereby forming an ion channel for conducting aluminum ions in the silicone rubber coating, thereby achieving uniform deposition of aluminum metal on the negative electrode surface and improving the uniformity of the aluminum metal layer deposited on the surface of the aluminum ion battery negative electrode; at the same time, by controlling the thickness of the silicone rubber and its derivatives to 0.1 μm to 20 μm Within this range, the exchange current density on the negative electrode surface can be regulated, and the exchange current density can be reduced as much as possible without affecting the limiting current density, so that the deposition uniformity of aluminum metal on the negative electrode surface of the aluminum ion battery can be more accurately regulated, and the uniformity of the aluminum metal layer deposited on the negative electrode surface of the aluminum ion battery can be further improved, and the deposition of large particles of aluminum and the formation of aluminum dendrites on the negative electrode surface of the aluminum ion battery can be reduced, and the reversibility and coulomb efficiency of the negative electrode deposition reaction of the aluminum ion battery can be improved, thereby reducing the occurrence of short circuit phenomenon in the aluminum ion battery and improving the cycle life and coulomb efficiency of the aluminum ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0017] Figure 1 This is a scanning electron microscope image of the negative electrode of the aluminum ion battery prepared in Example 1 of the present application;
[0018] Figure 2 This is a scanning electron microscope image of the negative electrode of the aluminum ion battery prepared in Example 2 of the present application;
[0019] Figure 3 The negative electrode of the aluminum ion battery prepared in Example 2 of the present application is 1 mA cm -2 Deposition at a current density of 1 mAh cm -2 SEM images after aluminum;
[0020] Figure 4 The aluminum ion battery negative electrode prepared in Example 2 of the present application is respectively at 3 mA cm -2 Deposition at a current density of 1 mAh cm -2 SEM images after aluminum;
[0021] Figure 5 The aluminum ion battery negative electrode prepared in Example 2 of the present application is respectively at 3 mA cm -2 , 5mA cm -2 Deposition at a current density of 1 mAh cm -2 Particle size distribution diagram of aluminum particles formed after aluminum;
[0022] Figure 6The battery assembled from the aluminum ion battery negative electrode prepared in Example 2 of the present application has a current density of 3 mA cm -2 Scanning electron microscope image of the membrane surface after 5 weeks of cycling at the current density;
[0023] Figure 7 The battery assembled from the aluminum ion battery negative electrode prepared in Example 2 of the present application has a current density of 3 mA cm -2 Scanning electron microscope image of the negative electrode surface after 5 weeks of cycling at the current density;
[0024] Figure 8 This is a scanning electron microscope image of the negative electrode of the aluminum ion battery prepared in Example 3 of the present application;
[0025] Fig. 9 This is a scanning electron microscope image of the negative electrode of the aluminum ion battery prepared in Example 4 of the present application;
[0026] Fig.10 This is a scanning electron microscope image of the aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of the present application;
[0027] Fig.11 The aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of this application is 1 mA cm -2 Deposition at a current density of 1 mAh cm -2 SEM image after aluminum;
[0028] Fig.12 The aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of this application is 3mA cm -2 Deposition at a current density of 1 mAh cm -2 SEM image after aluminum;
[0029] Fig.13 The aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of the present application is respectively at 3 mA cm -2 , 5mAcm -2 Particle size distribution diagram of aluminum particles formed by deposition under current density;
[0030] Fig.14 The battery assembled from the aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of this application is 3mAcm -2 Scanning electron microscope image of the membrane surface after 5 weeks of cycling at the current density;
[0031] Fig.15 The battery assembled from the aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of this application is 3mAcm -2 Scanning electron microscope image of the negative electrode surface after 5 weeks of cycling at the current density;
[0032] Fig.16The half-cell assembled with the negative electrode of the aluminum ion battery of Example 2 of the present application and Comparative Example 1 has a current density of 3 mA cm -2 , 3mAh cm -2 Comparison of Coulombic efficiency and cycle life under cycling conditions;
[0033] Fig.17 The half-cell assembled with the negative electrode of the aluminum ion battery of Example 2 of the present application and Comparative Example 1 has a current of 5 mA cm -2 , 5mAh cm -2 Comparison of Coulombic efficiency and cycle life under cycling conditions;
[0034] Fig.18 The symmetrical battery assembled from the aluminum ion battery negative electrode of Example 2 of the present application and Comparative Example 1 is 5 mA cm -2 , 5mAh cm -2 Comparison chart of cycle life under different cycle conditions;
[0035] Fig.19 The limiting current density distribution diagram of a symmetrical battery assembled with the aluminum ion battery negative electrode (pure aluminum foil negative electrode) provided in Comparative Example 2 of the present application;
[0036] Fig. 20 The limiting current density distribution diagram of a symmetrical battery assembled from an aluminum ion battery negative electrode with aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 0.3 μm provided in this application;
[0037] Fig.21 The limiting current density distribution diagram of a symmetrical battery assembled from an aluminum ion battery negative electrode with aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 1.0 μm provided in this application;
[0038] Fig. 22 The limiting current density distribution diagram of a symmetrical battery assembled from an aluminum ion battery negative electrode with aluminum foil as the negative electrode substrate and a silicone rubber coating thickness of 4.0 μm provided in this application;
[0039] Fig.23 The limiting current density distribution diagram of a symmetrical battery assembled from an aluminum ion battery negative electrode with aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 10.0 μm provided in this application;
[0040] Fig.24 A comparison chart of the exchange current density of a symmetrical battery assembled from the aluminum ion battery negative electrode with different silicone rubber coating thicknesses provided in the present application (with aluminum foil as the negative electrode substrate, the silicone rubber coating thicknesses are 0.3 μm, 1.0 μm, 4.0 μm and 10.0 μm respectively) and the aluminum ion battery negative electrode of Comparative Example 2;
[0041] Fig.25This is a comparison chart of the cycle life of a full battery assembled from the aluminum ion battery negative electrodes (pure aluminum foil negative electrodes) of Example 2 of the present application and Comparative Example 2. DETAILED DESCRIPTION
[0042] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0043] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0045] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0046] In a first aspect, an embodiment of the present application provides an aluminum ion battery negative electrode, which includes a negative electrode substrate and a coating located on the surface of the negative electrode substrate, wherein the coating includes silicone rubber and its derivatives, and the thickness of the coating is 0.1 μm to 20 μm.
[0047] In the above scheme, the negative electrode of the aluminum ion battery includes a negative electrode substrate and a silicone rubber and its derivative coating arranged on the negative electrode substrate. During the electrochemical deposition reaction of the negative electrode of the aluminum ion battery, the Si-O bonds in the silicone rubber and its derivative coating are partially destroyed in the electrolyte to form Al-O bonds, thereby forming ion channels that conduct aluminum ions in the silicone rubber coating, thereby achieving uniform deposition of aluminum metal on the surface of the negative electrode and improving the uniformity of the aluminum metal layer deposited on the surface of the negative electrode of the aluminum ion battery; at the same time, by controlling the thickness of the silicone rubber and its derivatives to 0.1 μm to 20 μm Within this range, the exchange current density on the negative electrode surface can be regulated, and the exchange current density can be reduced as much as possible without affecting the limiting current density, so that the deposition uniformity of aluminum metal on the negative electrode surface of the aluminum ion battery can be more accurately regulated, and the uniformity of the aluminum metal layer deposited on the negative electrode surface of the aluminum ion battery can be further improved, and the deposition of large particles of aluminum and the formation of aluminum dendrites on the negative electrode surface of the aluminum ion battery can be reduced, and the reversibility and coulomb efficiency of the negative electrode deposition reaction of the aluminum ion battery can be improved, thereby reducing the occurrence of short circuit phenomenon in the aluminum ion battery and improving the cycle life and coulomb efficiency of the aluminum ion battery.
[0048] In some embodiments, the thickness of the coating is 0.1 μm to 20 μm, specifically 0.1 μm, 0.2 μm, 0.3 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 8.0 μm, 10.0 μm, 12 μm, 15 μm, 18 μm or 20 μm, etc., of course, it can also be other values within the above range, which are not limited here. It can be understood that the thickness of the coating in the present application is within the above range, which can realize the regulation of the exchange current density on the surface of the negative electrode of the aluminum ion battery, and can reduce the exchange current density as much as possible without affecting the limiting current density, so that the deposition rate and uniformity of aluminum metal on the negative electrode surface of the aluminum ion battery can be more accurately regulated, and the uniformity of the aluminum metal layer deposited on the negative electrode surface of the aluminum ion battery can be further improved, and the deposition of large particles of aluminum on the negative electrode surface of the aluminum ion battery and the generation of aluminum dendrites can be reduced, so that the occurrence of short circuit phenomenon in the aluminum ion battery can be reduced and the cycle life and coulomb efficiency of the aluminum ion battery can be improved. Preferably, the thickness of the coating is 0.2 μm to 2.0 μm.
[0049] In some embodiments, silicone rubber and its derivatives include at least one of polydimethylsiloxane, methylvinyl silicone rubber, phenyl silicone rubber, fluorosilicone rubber and nitrile silicone rubber. It is understandable that the present application uses silicone rubber and its derivatives as a coating, and the Si-O bonds in the coating will be partially destroyed in the electrolyte to form Al-O bonds, thereby forming an ion channel that conducts aluminum ions and anions, thereby enabling uniform deposition of aluminum metal on the negative electrode surface and improving the uniformity of the aluminum metal layer deposited on the negative electrode surface of the aluminum ion battery; at the same time, the aluminum metal is connected to the coating through a chemical bond, which can make the negative electrode structure of the aluminum ion battery more stable, and can reduce the risk of aluminum metal falling off during the battery cycle, which is beneficial to improving the cycle stability of the battery.
[0050] In some embodiments, the negative electrode substrate includes at least one of aluminum foil, copper foil, stainless steel foil, titanium foil, nickel foil, molybdenum foil, nickel foam, copper foam, and aluminum foam.
[0051] In a second aspect, the present application provides a method for preparing an aluminum ion battery negative electrode according to the first aspect, comprising the following steps:
[0052] A silicone rubber precursor slurry with a mass concentration of 0.01 g / mL to 0.75 g / mL is coated on the surface of a negative electrode substrate, and cured and dried to obtain an aluminum ion battery negative electrode. The aluminum ion battery negative electrode includes a negative electrode substrate and a coating located on the surface of the negative electrode substrate, and the coating includes silicone rubber and its derivatives.
[0053] In the above scheme, the thickness of the coating formed on the surface of the negative electrode substrate can be controlled by controlling the mass concentration of the silicone rubber precursor slurry. The aluminum ion battery negative electrode of the present application has a simple preparation process and is easy to mass produce.
[0054] In some embodiments, the silicone rubber precursor slurry can be obtained by dissolving the silicone rubber precursor in a solvent, wherein the solvent includes but is not limited to ethyl acetate, butyl acetate, n-hexane, cyclohexane, toluene, and xylene, which can be selected according to actual needs and are not limited here.
[0055] In some embodiments, the silicone rubber precursor includes at least one of polydimethylsiloxane, methylvinyl silicone rubber, phenyl silicone rubber, fluorosilicone rubber, and nitrile silicone rubber.
[0056] In some embodiments, the mass concentration of the silicone rubber precursor slurry is 0.01 g / mL to 0.75 g / mL, specifically 0.01 g / mL, 0.05 g / mL, 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.5 g / mL, 0.6 g / mL, 0.7 g / mL or 0.75 g / mL, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable. In the present application, the thickness of the silicone rubber and its derivative coating can be controlled by controlling the mass concentration of the silicone rubber precursor slurry.
[0057] In some embodiments, the curing and drying temperature is 25°C to 140°C, specifically 25°C, 30°C, 50°C, 80°C, 100°C, 120°C, 130°C or 140°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0058] In some embodiments, the curing and drying time is 2 h to 48 h, specifically 2 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 24 h, 30 h, 36 h, 40 h or 48 h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0059] In the present application, by controlling the curing and drying time and temperature of the silicone rubber precursor, it is beneficial to improve the uniformity, density and adhesion of the silicone rubber and its derivative coating on the surface of the negative electrode substrate.
[0060] In a third aspect, an embodiment of the present application provides an aluminum ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that the negative electrode is the above-mentioned aluminum ion battery negative electrode or the aluminum ion battery negative electrode prepared according to the above-mentioned preparation method.
[0061] In the above scheme, the negative electrode of the aluminum ion battery can be obtained by assembling the positive electrode, the negative electrode, the electrolyte and the separator. It is understandable that there is no particular limitation on the assembly method of the negative electrode, the electrolyte, the separator and the positive electrode, and conventional assembly methods can be used.
[0062] In some embodiments, the aluminum ion battery can be a symmetrical battery, a half-cell, or a full-cell, which is not limited herein.
[0063] In some embodiments, the positive electrode includes but is not limited to graphite, porphyrin, quinone, Prussian blue, etc., which can be selected according to actual needs and are not limited here.
[0064] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on a surface of the positive electrode current collector.
[0065] In some embodiments, the electrolyte comprises an ionic liquid electrolyte and / or a deep eutectic solvent.
[0066] In some embodiments, the electrolyte is an ionic liquid electrolyte, and the ionic liquid electrolyte includes an aluminum chloride and an imidazole salt system. The molar ratio of aluminum chloride to imidazole salt is 1.3: 1. Specifically, the ionic liquid electrolyte can be at least one of aluminum chloride and 1-ethyl-3-methylimidazolium chloride, aluminum chloride and 1-propyl-3-methylimidazolium chloride, aluminum chloride and imidazole bromide, and aluminum chloride and imidazole iodide, which can be selected according to actual needs and are not limited here.
[0067] In some embodiments, the electrolyte is a deep eutectic solvent, and the deep eutectic solvent includes at least one of aluminum chloride and caprolactam, aluminum chloride and urea, aluminum chloride and N-alkyl urea, aluminum chloride and acetamide, aluminum chloride and triethylamine, aluminum chloride and pyridine, aluminum chloride and pyridine chloride, aluminum chloride and alkylamine hydrochloric acid, aluminum chloride and acrylamide, and aluminum chloride and thiourea.
[0068] In some embodiments, the separator of the aluminum ion battery may be a conventional separator, for example, a porous polymer film or an inorganic porous film, and exemplary separators are, for example, one or more of a porous polypropylene film, a porous polyethylene film, a porous composite polymer film, a non-woven fabric, a glass fiber paper, or a porous ceramic separator.
[0069] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0070] Example 1
[0071] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is polydimethylsiloxane (PDMS) and has a thickness of 0.3 μm.
[0072] The preparation method is as follows:
[0073] A polydimethylsiloxane (PDMS) slurry with a mass concentration of 0.05 g / mL was coated on the surface of the copper foil and dried at 120° C. for 4 h to obtain an aluminum ion battery negative electrode.
[0074] The morphology of the aluminum ion battery negative electrode prepared in this embodiment was characterized by scanning electron microscopy. The morphology of the polydimethylsiloxane (PDMS) coating is as follows: Figure 1 shown.
[0075] Example 2
[0076] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is polydimethylsiloxane (PDMS) and has a thickness of 1.0 μm.
[0077] The preparation method is as follows:
[0078] A polydimethylsiloxane (PDMS) slurry with a mass concentration of 0.1 g / mL was coated on the surface of the copper foil and dried at 120° C. for 4 h to obtain an aluminum ion battery negative electrode.
[0079] The morphology of the aluminum ion battery negative electrode prepared in this embodiment was characterized by scanning electron microscopy. The morphology of the polydimethylsiloxane (PDMS) coating is as follows: Figure 2 shown.
[0080] Figure 3 The negative electrode of the aluminum ion battery prepared in Example 2 is 1 mA cm -2 Deposition at a current density of 1 mAh cm -2 SEM images after aluminum; Figure 4 The aluminum ion battery negative electrode prepared in Example 2 is 3 mA cm -2 Deposition at a current density of 1 mAh cm -2 Aluminum after the scanning electron microscope image; Figure 3 , Figure 4 As shown, the aluminum deposited on the surface of the negative electrode of the aluminum ion battery in this embodiment has a smooth and uniform morphology, and there are no obvious large particles of aluminum.
[0081] Figure 5 The aluminum ion battery negative electrode prepared in Example 2 of the present application is respectively at 3 mA cm -2 , 5mA cm -2 Deposition at a current density of 1 mAh cm -2 The particle size distribution diagram of aluminum particles formed after aluminum is Figure 5 As shown in the figure, the aluminum particles deposited on the negative electrode surface of the aluminum ion battery in this embodiment have a small particle size and are -2 The average particle size of aluminum particles deposited under the current density is only 4.3 μm. -2 The average particle size of the aluminum particles deposited under the current density is only 1.8μm.
[0082] Figure 6 The battery assembled from the aluminum ion battery negative electrode prepared in this embodiment is 3mA cm -2 Scanning electron microscope image of the membrane surface after 5 weeks of cycling at the current density; Figure 7 The battery assembled from the aluminum ion battery negative electrode prepared in Example 2 of the present application has a current density of 3 mA cm -2 Scanning electron microscope image of the negative electrode surface after 5 weeks of cycling at the current density; Figure 6 , Figure 7 As shown, the surfaces of the separator and the negative electrode are clean and free of dead aluminum residue after cycling.
[0083] Example 3
[0084] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is polydimethylsiloxane (PDMS) and has a thickness of 4.0 μm.
[0085] The preparation method is as follows:
[0086] A polydimethylsiloxane (PDMS) slurry with a mass concentration of 0.2 g / mL was coated on the surface of the copper foil and dried at 120° C. for 4 h to obtain an aluminum ion battery negative electrode.
[0087] The morphology of the aluminum ion battery negative electrode prepared in this embodiment was characterized by scanning electron microscopy. The morphology of the polydimethylsiloxane (PDMS) coating is as follows: Figure 8 shown.
[0088] Example 4
[0089] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is polydimethylsiloxane (PDMS) and has a thickness of 10.0 μm.
[0090] The preparation method is as follows:
[0091] A polydimethylsiloxane (PDMS) slurry with a mass concentration of 0.5 g / mL was coated on the surface of the copper foil and dried at 120° C. for 4 h to obtain an aluminum ion battery negative electrode.
[0092] The morphology of the aluminum ion battery negative electrode prepared in this embodiment was characterized by scanning electron microscopy. The morphology of the polydimethylsiloxane (PDMS) coating is as follows: Fig. 9 shown.
[0093] Example 5
[0094] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is polydimethylsiloxane (PDMS) and has a thickness of 0.1 μm.
[0095] The preparation method is as follows:
[0096] A polydimethylsiloxane (PDMS) slurry with a mass concentration of 0.01 g / mL was coated on the surface of the copper foil and dried at 120° C. for 4 h to obtain an aluminum ion battery negative electrode.
[0097] Example 6
[0098] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is polydimethylsiloxane (PDMS) and has a thickness of 20.0 μm.
[0099] The preparation method is as follows:
[0100] A polydimethylsiloxane (PDMS) slurry with a mass concentration of 0.75 g / mL was coated on the surface of the copper foil and dried at 120° C. for 4 h to obtain an aluminum ion battery negative electrode.
[0101] Example 7
[0102] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is methyl vinyl silicone rubber and has a thickness of 1.0 μm.
[0103] The negative electrode of the aluminum ion battery was prepared in the same manner as in Example 2, except that the silicone rubber used was replaced by methyl vinyl silicone rubber instead of polydimethylsiloxane (PDMS).
[0104] Example 8
[0105] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is phenyl silicone rubber and has a thickness of 1.0 μm.
[0106] The aluminum ion battery negative electrode was prepared in the same manner as in Example 2, except that the silicone rubber used was replaced by phenyl silicone rubber instead of polydimethylsiloxane (PDMS).
[0107] Example 9
[0108] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is fluorosilicone rubber and has a thickness of 1.0 μm.
[0109] The aluminum ion battery negative electrode was prepared in the same manner as in Example 2, except that the silicone rubber used was replaced by fluorosilicone rubber instead of polydimethylsiloxane (PDMS).
[0110] Example 10
[0111] A negative electrode for an aluminum ion battery comprises a copper foil and a coating on the surface of the copper foil, wherein the coating is nitrile silicone rubber and has a thickness of 1.0 μm.
[0112] The aluminum ion battery negative electrode was prepared in the same manner as in Example 2, except that the silicone rubber used was replaced by nitrile silicone rubber instead of polydimethylsiloxane (PDMS).
[0113] Comparative Example 1
[0114] Copper foil is directly used as the negative electrode of aluminum ion battery.
[0115] The surface morphology of the copper foil negative electrode of this comparative example 1 was characterized by scanning electron microscopy. Fig.10 shown.
[0116] Fig.11The negative electrode of the aluminum ion battery prepared in this comparative example 1 is 1 mA cm -2 Deposition at a current density of 1 mAh cm -2 SEM images after aluminum; Fig.12 The negative electrode of the aluminum ion battery prepared in this comparative example has a conductivity of 3 mA cm -2 Deposition at a current density of 1 mAh cm -2 Aluminum after the scanning electron microscope image; Fig.11 , Fig.12 As shown, the aluminum deposited on the negative electrode surface of the aluminum ion battery in this comparative example has poor flatness and uneven deposition, and obviously larger particles of aluminum are deposited; Fig.11 , Fig.12 and Figure 3 , Figure 4 By comparison, it can be seen that compared with directly using pure copper foil as the negative electrode of the aluminum ion battery, the present application sets a silicone rubber coating on the surface of the negative electrode substrate (i.e., copper foil). Under the same current density and deposition capacity, aluminum with a smoother and more uniform morphology and smaller grains can be deposited on the surface of the negative electrode of the aluminum ion battery, which is beneficial to improving the reversibility of the deposition reaction of the negative electrode of the aluminum ion battery.
[0117] Fig.13 The negative electrode of the aluminum ion battery prepared in this comparative example is 3mA cm -2 , 5mA cm -2 The particle size distribution of aluminum particles deposited under current density is shown in Figure 2. Fig.13 As shown in the figure, the particle size of the aluminum particles deposited on the negative electrode surface of the aluminum ion battery in this embodiment is relatively large. -2 The average particle size of the aluminum particles deposited under the current density is 10.2 μm. -2 The average particle size of aluminum particles deposited under the current density is 7.1 μm. Fig.13 and Figure 5 By comparison, it can be seen that the aluminum particles deposited on the negative electrode surface of the aluminum ion battery in Example 2 of the present application have a -2 The average particle size of the aluminum particles deposited under the current density is only half of that of Comparative Example 1. -2 The average particle size of the aluminum particles deposited under the current density is only 1 / 4 of that in comparative example 1, indicating that the aluminum ion battery negative electrode of the present application can reduce the generation of large aluminum particles on the surface of the aluminum ion battery negative electrode during the electrochemical deposition process by providing a silicone rubber coating on the surface of the negative electrode substrate (i.e., copper foil), thereby facilitating the improvement of the cycle life and coulomb efficiency of the aluminum ion battery.
[0118] Fig.14 The battery assembled from the aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of this application is 3mAcm -2Scanning electron microscope image of the membrane surface after 5 weeks of cycling at the current density; Fig.15 The battery assembled from the aluminum ion battery negative electrode (pure copper foil negative electrode) provided in Comparative Example 1 of the present application has a current of 3 mA cm -2 Scanning electron microscope image of the negative electrode surface after 5 weeks of cycling at the current density; Fig.14 , Fig.15 As shown in the figure, there is a lot of dead aluminum on the surface of the separator and the negative electrode during the cycle, which is the cause of the battery short circuit. Figure 6 , Figure 7 and Fig.14 , Fig.15 By comparing the test results, it can be seen that the present application can reduce the dead aluminum on the diaphragm and the negative electrode surface of the aluminum ion battery negative electrode during the cycle process by arranging a silicone rubber coating on the surface of the negative electrode substrate, thereby significantly improving the reversibility of the negative electrode deposition reaction of the aluminum ion battery and improving the cycle life and coulombic efficiency of the aluminum ion battery.
[0119] The negative electrode of the aluminum ion battery prepared in Example 2 and Comparative Example 1 was used as the working electrode and the pure aluminum sheet was used as the counter electrode to assemble a half-cell. - 3 mAh cm deposited at a current density of 2 -2 After aluminum, the half-cell was tested for deposition / dissolution of the negative electrode reaction. The test results are as follows Fig.16 shown. Fig.16 The half-cell assembled with the negative electrode of the aluminum ion battery of Example 2 of the present application and Comparative Example 1 has a current density of 3 mA cm -2 , 3mAh cm -2 Comparison of Coulombic efficiency and cycle life under cycling conditions; Fig.16 It can be seen that the aluminum ion battery using pure copper foil as the negative electrode in Comparative Example 1 will short-circuit within 30 hours, and the coulombic efficiency is less than 99%. The reason for the short-circuit is that the large aluminum particles produced by aluminum deposition penetrate the diaphragm; Example 2 uses silicone rubber + copper foil aluminum negative electrode reaction, which can be cycled for more than 1700 hours, and the coulombic efficiency is 99.9%.
[0120] The negative electrode of the aluminum ion battery prepared in Example 2 and Comparative Example 1 was used as the working electrode and the pure aluminum sheet was used as the counter electrode to assemble a half-cell. The half-cell was subjected to 5 mA cm -2 Deposition at a current density of 5 mAh cm -2 After aluminum, the half-cell was tested for deposition / dissolution of the negative electrode reaction. The test results are as follows Fig.17 shown. Fig.17 The negative electrode of the aluminum ion battery of Example 2 and Comparative Example 1 of the present application is 5 mA cm -2 , 5mAh cm -2 Comparison of Coulombic efficiency and cycle life under cycling conditions; Fig.21It can be seen that the aluminum ion battery using pure copper foil as the negative electrode in comparative example 1 will short-circuit within 20 hours; the aluminum negative electrode reaction using silicone rubber + copper foil in example 2 can cycle for more than 900 hours, and the coulomb efficiency is 99.8%.
[0121] according to Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Fig.11 , Fig.12 , Fig.13 , Fig.14 , Fig.15 , Fig.16 and Fig.17 By comparing and comprehensively analyzing the test results, it can be seen that the present application can reduce the generation of large aluminum particles on the negative electrode surface of aluminum ion batteries and reduce the generation of dead aluminum on the diaphragm and negative electrode surfaces during the cycle by arranging a silicone rubber coating on the surface of the negative electrode substrate, thereby improving the reversibility of the negative electrode deposition reaction of aluminum ion batteries, reducing the occurrence of short circuits during the cycle of aluminum ion batteries, and improving the cycle life and coulomb efficiency of aluminum ion batteries.
[0122] The aluminum ion battery negative electrodes prepared in Example 2 and Comparative Example 1 were respectively heated at 5 mA cm -2 Deposition at a current density of 5 mAh cm -2 After aluminum, the negative electrode of the aluminum ion battery deposited in Example 2 and Comparative Example 1 was used as the working electrode, and the pure aluminum sheet was used as the counter electrode to assemble a symmetrical battery. Then, the symmetrical battery was subjected to a deposition / dissolution negative electrode reaction test. The test results are as follows: Fig.18 shown. Fig.18 The symmetrical battery assembled from the aluminum ion battery negative electrode of Example 2 of the present application and Comparative Example 1 is 5 mA cm -2 , 5mAh cm -2 The cycle life comparison chart under the cycle conditions of Fig.18 It can be seen that the aluminum ion battery coated with the silicone rubber coating in Example 2 can be cycled for 2800 hours, while the uncoated aluminum ion battery in Comparative Example 1 will short-circuit within 15 hours. This shows that coating the surface of the negative electrode substrate with a silicone rubber coating can reduce the occurrence of short circuits during the cycle of the aluminum ion battery and can increase the cycle life of the aluminum ion battery.
[0123] Comparative Example 2
[0124] Aluminum foil is directly used as the negative electrode of aluminum ion battery.
[0125] Fig.19 The limiting current density distribution diagram of a symmetrical battery assembled with the aluminum ion battery negative electrode (pure aluminum foil negative electrode) provided in Comparative Example 2 of the present application; Fig.19As shown in the figure, the limiting current density of the pure aluminum foil negative electrode assembled into a battery can reach 7.0 mA cm -2 .
[0126] Fig. 20 The limiting current density distribution diagram of a symmetrical battery assembled with an aluminum ion battery negative electrode provided in this application using aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 0.3 μm; Fig. 20 As shown in Figure 2, when the thickness of the silicone rubber coating on the aluminum foil surface is 0.3 μm, the limiting current density tested after the aluminum ion battery negative electrode is assembled into a battery can reach 7 mA cm -2 about.
[0127] Fig.21 The limiting current density distribution diagram of a symmetrical battery assembled with an aluminum ion battery negative electrode provided in this application using aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 1.0 μm; Fig.21 As shown in Figure 2, when the thickness of the silicone rubber coating on the aluminum foil surface is 1.0 μm, the limiting current density tested after the aluminum ion battery negative electrode is assembled into a battery can reach 7 mA cm -2 about.
[0128] Fig. 22 The limiting current density distribution diagram of a symmetrical battery provided in this application, which is assembled with an aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 4.0 μm for an aluminum ion battery negative electrode; Fig. 22 As shown in Figure 2, when the thickness of the silicone rubber coating on the aluminum foil surface is 4.0 μm, the limiting current density tested after the aluminum ion battery negative electrode is assembled into a battery is 0.9 mA cm -2 about.
[0129] Fig.23 The limiting current density distribution diagram of a symmetrical battery assembled with an aluminum ion battery negative electrode provided in this application using aluminum foil as the negative electrode substrate and a silicone rubber coating with a thickness of 10.0 μm; Fig.23 As shown in Figure 2, when the thickness of the silicone rubber coating on the aluminum foil surface is 4.0 μm, the limiting current density tested after the aluminum ion battery negative electrode is assembled into a battery is 0.4 mA cm -2 about.
[0130] Fig.24 A comparison chart of the exchange current density of a symmetrical battery assembled from an aluminum ion battery negative electrode with different silicone rubber coating thicknesses provided in the present application (with aluminum foil as the negative electrode substrate, and the silicone rubber coating thicknesses are 0.3μm, 1.0μm, 4.0μm and 10.0μm, respectively) and the aluminum ion battery negative electrode of Comparative Example 2.
[0131] Will Fig. 20 , Fig.21 , Fig. 22 and Fig.23The test results and Fig.19 , Fig.24 By comparing the test results of , it can be seen that the thickness of the silicone rubber coating on the negative electrode surface of the aluminum ion battery has a great influence on the limiting current density and exchange current density during the electrochemical deposition process. Fig. 20 , Fig.21 , Fig. 22 and Fig.23 The test results and Fig.19 By comparing the test results, it can be seen that the limiting current density when the thickness of the silicone rubber coating on the surface of the negative electrode substrate (aluminum foil) is 0.3μm and 1.0μm is consistent with that when the surface of the negative electrode substrate (aluminum foil) is uncoated in Comparative Example 2, indicating that the silicone rubber coating with a thickness of less than 1.0μm has little effect on the limiting current density. However, when the thickness of the silicone rubber coating applied on the surface of the negative electrode substrate (aluminum foil) increases, the limiting current density may also increase, such as Fig. 22 As shown in Figure 2, when the thickness of the silicone rubber coating on the surface of the negative electrode substrate (aluminum foil) increases to 4.0 μm, the limiting current density decreases to 0.9 mA cm -2 ,like Fig.23 As shown in Figure 2, when the thickness of the silicone rubber coating on the surface of the negative electrode substrate (aluminum foil) increases to 10.0 μm, the limiting current density decreases to 0.4 mA cm -2 ; This indicates that the excessively thick silicone rubber coating on the surface of the negative electrode substrate has a significant impact on the limiting current density, which is not conducive to improving the performance of aluminum ion batteries.
[0132] In addition, from Fig.24 It can be seen that when the thickness of the silicone rubber coating on the surface of the negative electrode substrate increases, the exchange current density will decrease accordingly, and the reduction of the exchange current density is beneficial to the improvement of battery performance. Therefore, in practical applications, it is more preferred that the thickness of the silicone rubber coating applied on the surface of the negative electrode substrate is less than or equal to 1.0μm, which does not affect the limiting current density and has a lower exchange current density, which is beneficial to the improvement of battery performance.
[0133] The aluminum ion battery negative electrode prepared in Example 2 and Comparative Example 2 was charged at 1200 mA cm -2 Deposition at a current density of 2.4 mAh cm -2 After aluminum, the aluminum ion battery negative electrode and graphite positive electrode material were assembled into a full battery for testing. The test results are as follows Fig.25 As shown, Fig.25 This is a comparison chart of the cycle life of the full battery assembled from the aluminum ion battery negative electrodes of Example 2 of the present application and Comparative Example 2. It can be seen from the figure that the aluminum negative electrode coated with silicone rubber in Example 2 can be cycled more than 2500 times, while the uncoated aluminum negative electrode in Comparative Example 2 can only be stably cycled for 500 cycles. This shows that coating the surface of the negative electrode substrate with silicone rubber is beneficial to improving the cycle life of the aluminum ion battery.
[0134] Test method:
[0135] (1) Characterization test of aluminum ion battery negative electrode deposition morphology:
[0136] The aluminum ion battery negative electrode prepared in the embodiments and comparative examples of the present application is used as the working electrode, pure copper foil is used as the counter electrode, a polytetrafluoroethylene (PTFE) sheet or a glass fiber sheet membrane with a central hole is used as the diaphragm, and AlCl3-EMIMCl (molar ratio 1.3:1) ionic liquid is used as the electrolyte to assemble into a button cell, and the button cell is deposited with a certain capacity at a certain current density.
[0137] (2) Aluminum ion battery negative electrode limiting current density test:
[0138] Two aluminum foils coated with silicone rubber coatings of different thicknesses were used as the negative electrode of aluminum ion batteries, and a glass fiber separator (Whatman GF / C) and AlCl3-EMIMCl (1.3:1) ionic liquid electrolyte were assembled into a symmetrical battery. The limiting current density was characterized by the gradient constant current method, and the constant current was set to 0.1 mA cm -2 , 0.2 mA cm -2 , 0.3 mA cm -2 , 0.4 mA cm -2 , 0.5 mA cm -2 , 0.6 mA cm -2 , 0.7 mA cm -2 , 0.8 mA cm -2 , 0.9 mA cm -2 , 1.0 mA cm -2 , 1.5 mA cm -2 , 2.0mAcm -2 , 2.5 mA cm -2 , 3.0mA cm -2 , 3.5 mA cm -2 , 4.0mA cm -2 , 4.5 mA cm -2 , 5.0mA cm -2 , 6.0mA cm -2 , 7.0mA cm -2 , 8.0mA cm -2 , 9.0mA cm -2 , 10.0 mA cm -2 The deposition and dissolution reactions were set up 10 times for each current density. When the current density increases to the limiting current density value, dendrites are generated on the electrode surface and short circuits are induced. The limiting current density can be inferred based on the short-circuit current density.
[0139] (3) Aluminum ion battery negative electrode exchange current density test:
[0140] Two aluminum foils coated with different thicknesses of silicone rubber coating were used as the negative electrode of aluminum ion battery, and glass fiber separator (Whatman GF / C) and AlCl3-EMIMCl (1.3:1) ionic liquid electrolyte were assembled into a symmetrical battery. Then the symmetrical battery was used for cyclic voltammetry test, and Tafel curve was made to obtain the exchange current density of the negative electrode of aluminum ion battery with different thicknesses of silicone rubber coating.
[0141] (4) Electrochemical performance test
[0142] Half-cell test: 200 μm aluminum foil is used as the counter electrode to provide an aluminum source, the aluminum ion battery negative electrode prepared in the embodiment and comparative example of the present application is used as the working electrode, and the glass fiber separator (Whatman GF / C) and AlCl3-EMIMCl (1.3:1) ionic liquid electrolyte are assembled into an Al-Cu half-cell. Test method: Deposit a specific capacity at a specific constant current density, and then charge and dissolve at a specific constant current density, the cut-off potential is set to 0.6 V, and the coulomb efficiency = Q (dissolution capacity) / Q (deposition capacity) * 100%.
[0143] Symmetrical battery test: Use 200 μm aluminum foil as the counter electrode, provide an aluminum source, use the aluminum ion battery negative electrode prepared in the embodiment and comparative example of the present application as the working electrode, and assemble an Al-Cu battery with a glass fiber separator (Whatman GF / C) and AlCl3-EMIMCl (1.3:1) ionic liquid electrolyte. Or use Al foil coated with silicone rubber as both the working electrode and the counter electrode to assemble a symmetrical battery. Test method: First, deposit 3 mAh cm on the copper foil coated with silicone rubber. -2 The aluminum is then deposited and dissolved at a specific constant current and capacity, and the symmetrical battery deposition and dissolution curves are observed to determine the cycle life.
[0144] Table 1 Electrochemical performance test results of the aluminum ion battery negative electrode prepared in the examples and comparative examples
[0145]
[0146] According to the test data in Table 1, the aluminum ion battery negative electrode of the present application is provided with a silicone rubber and its derivative coating on the negative electrode substrate. During the electrochemical deposition reaction of the aluminum ion battery negative electrode, the Si-O bond in the silicone rubber and its derivative coating is partially destroyed in the electrolyte to form an Al-O bond, thereby forming an ion channel for conducting aluminum ions, so that the aluminum metal can be uniformly deposited on the negative electrode surface, and the uniformity of the aluminum metal layer deposited on the negative electrode surface of the aluminum ion battery is improved; at the same time, by controlling the thickness of the silicone rubber and its derivatives within the range of 0.1 μm to 20 μm, the exchange current density of the negative electrode can be regulated, and the exchange current density can be reduced as much as possible without affecting the limiting current density, so that the deposition rate and deposition uniformity of the aluminum metal on the negative electrode surface of the aluminum ion battery can be more accurately regulated, and the uniformity of the aluminum metal layer deposited on the negative electrode surface of the aluminum ion battery can be further improved. The deposition of large-particle aluminum on the negative electrode surface and the generation of aluminum dendrites are reduced, thereby reducing the occurrence of short circuit phenomenon in the aluminum ion battery and improving the cycle life and first coulomb efficiency of the aluminum ion battery.
[0147] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An aluminum ion battery negative electrode, characterized in that: The aluminum ion battery negative electrode comprises a negative electrode substrate and a coating located on the surface of the negative electrode substrate. The coating comprises silicone rubber and its derivatives. The thickness of the coating is 0.1 μm to 20 μm.
2. The aluminum ion battery negative electrode according to claim 1, characterized in that: The silicone rubber and its derivatives include at least one of polydimethylsiloxane, methylvinyl silicone rubber, phenyl silicone rubber, fluorosilicone rubber and nitrile silicone rubber.
3. The aluminum ion battery negative electrode according to claim 1, characterized in that: The coating has a thickness of 0.2 μm to 2 μm.
4. The aluminum ion battery negative electrode according to claim 1, characterized in that: The negative electrode substrate includes at least one of aluminum foil, copper foil, stainless steel foil, titanium foil, nickel foil, molybdenum foil, foamed nickel, foamed copper and foamed aluminum.
5. An aluminum ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The negative electrode is the negative electrode for an aluminum ion battery according to any one of claims 1 to 4.
6. The aluminum ion battery according to claim 5, characterized in that: The electrolyte includes an ionic liquid electrolyte and / or a deep eutectic solvent.
7. The aluminum ion battery according to claim 6, characterized in that: The ionic liquid electrolyte comprises an aluminum chloride and an imidazole salt system.
8. The aluminum ion battery according to claim 6, characterized in that: The deep eutectic solvent includes at least one of aluminum chloride and caprolactam, aluminum chloride and urea, aluminum chloride and N-alkylurea, aluminum chloride and acetamide, aluminum chloride and triethylamine, aluminum chloride and pyridine, aluminum chloride and pyridine chloride, aluminum chloride and alkylamine hydrochloric acid, aluminum chloride and acrylamide, and aluminum chloride and thiourea.
Citation Information
Patent Citations
Electrode current collector, preparation method thereof, negative electrode and lithium ion battery
CN109830691A
Composite artificial solid-state electrolyte interface film modified negative electrode material and battery application thereof
CN111463403A
Improved electrodes for energy storage devices
US20240145727A1
Cited By
Lithium battery ester electrolyte with moisture-proof function as well as preparation method and application of lithium battery ester electrolyte
CN119994181A